Analysis of Linguo-cultural Picture of LIE in Systemic Data - Snukiškienė, Irena (Vilnius University Open Series, 2021)
The article presents Lithuanian linguistic cultural image of LIE (MELAS) reconstructed from lexicographic data. The analysis of the lexicographic definitions of this lexeme in Lithuanian dictionaries (The Dictionary of Lithuanian Language, The Dictionary of Contemporary Lithuanian, the dictionaries of synonyms and antonyms and Lithuanian etymological sources) provides two views of the concept: synchronic and diachronic. The diachronic view shows the semantic development of the word, the specification of its meaning (the loss of the primary and the acquisition of new meanings). The synchronic view shows the basic meaning of the concept and its profiles in contemporary language. The research revealed that the basic meaning is LIE as a subject’s purposeful distortion of reality with the purpose of deception. The dominating aspects are: a subject’s purposeful activity and an object that a subject wants to deceive. Lexicographic data distinguished several profiles of LIE: (1) LIE as entertainment (when lie is used for joking, visual storytelling and has no negative purpose), (2) LIE as unethical issue (when lying is seen as negative, sinister activity) and (3) LIE as psychologically necessary element of life (when lie is seen as useful, helping to get out of difficult situations). The analysis is concluded with the cognitive definition of lie, providing its linguo-cultural view in Lithuanian.
Keywords: lie; basic meaning; profile; linguistic worldview; lexicography